M1 Do climate changes influence environmental aspergillus fumigatus load at the manchester university NHS foundation trust adult cystic fibrosis centre?. (12th November 2019) - Coleman, JA; Jones, AM; Collier, LJ; Richardson, MD; Bright-Thomas, RJ
Abstract : Aspergillus fumigatus is a ubiquitous opportunistic fungal pathogen found commonly in the outside and indoor environments. It is known to cause allergic disease in patients with cystic fibrosis (CF) who, unlike unaffected individuals, are less able to clear spores. There is little literature looking at the relationships between the amount of Aspergillus fumigatus in the environment and the weather. This study investigates how the Aspergillus levels in the environment of the Manchester Adult CF Centre vary with climate. Methods: Air samples were analysed from nine areas outside and within the Manchester Adult CF Centre, with at least 15 samples taken in each area over a 14-month period. Climatic information including mean, maximum, and minimum temperature and humidity, sunshine hours, mean wind speed and maximum gust, and rainfall, were obtained from a nearby meteorological office weather monitoring station. The Aspergillus fumigatus spore counts were then correlated with the 10 different meteorological factors to identify any associations. Results: The outdoor Aspergillus level was positively correlated to the daily maximum and mean temperature (r=0.378 p=0.015 and r=0.356 p<0.022 respectively) and negatively correlated to mean wind speed and maximum gust (r=-0.465 p=0.002, and r-0.427, p=0.005) on the day of sampling. Indoor Aspergillus levels also correlated with wind speed and gust, and maximum temperature, in a number of areas on the ward. Aspergillus counts were dramatically lower throughout the sampling period in an area on the ward with high air exchange rates. Maximum temperature; mean wind speed and maximum gust on the day before sampling were also correlated with outdoor Aspergillus level (r=0.372 p<0.016, r=-0.374 p=0.016 and r=-0.342 p=0.029 respectively). Rainfall, sunshine and relative humidity were not related to outdoor Aspergillus level (p>0.05). Conclusion: The environmental A spergillus fumigatus burden is positively associated with increased temperature and negatively associated with wind speed. Temporal changes in weather parameters appear to influence Aspergillus fumigatus burden for a subsequent 24 hour period. Climatic conditions will influence exposure to this pathogen for susceptible individuals, including patients with CF.